2017
DOI: 10.1074/jbc.m116.747618
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Glioblastoma Nanovesicles Contain Intracellular Signaling Proteins and Active Ras Incorporated in a Farnesylation-dependent Manner

Abstract: Edited by Alex TokerGlioblastomas (GBMs) are malignant brain tumors with a median survival of less than 18 months. Redundancy of signaling pathways represented within GBMs contributes to their therapeutic resistance. Exosomes are extracellular nanovesicles released from cells and present in human biofluids that represent a possible biomarker of tumor signaling state that could aid in personalized treatment. Herein, we demonstrate that mouse GBM cell-derived extracellular nanovesicles resembling exosomes from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 89 publications
1
36
0
Order By: Relevance
“…Numerous evidences suggest that the occurrence of glioma is related with the activation of multiple oncogenes, including Ras family genes [3]. The family of Ras contains three members: K-Ras, H-Ras, and N-Ras.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous evidences suggest that the occurrence of glioma is related with the activation of multiple oncogenes, including Ras family genes [3]. The family of Ras contains three members: K-Ras, H-Ras, and N-Ras.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous publication, we demonstrated that GBM exosomes are enriched for signaling proteins and contain active GTP-bound Ras, and that active Ras interacts with exosome proteins based on GST-Raf-RBD pulldown data [ 1 ]. In light of these results, we wondered whether GBM exosomes are taken up by other GBM cells to influence their signaling status.…”
Section: Resultsmentioning
confidence: 99%
“…Exosomes are tiny (50-150nm) extracellular vesicles (EVs) implicated in cell-to-cell communication. When compared to intact cells, these vesicles are enriched for membrane-associated signaling and cell communication proteins [ 1 ], and have been proposed to alter a number of cellular processes, such as prion protein transmission and neurodegenerative diseases [ 2 ], regulation of immune functions [ 3 ], tumor angiogenesis [ 4 ā€“ 16 ], fibroblast signaling to tumors [ 17 , 18 ], and priming of the metastatic niche [ 19 ā€“ 26 ]. In addition to lipids and proteins, these vesicles carry DNA and RNA [ 13 , 27 ā€“ 29 ] and are present in biofluids; hence, research is underway to harness these carriers of cell communication cargoes to identify signatures that could be useful biomarkers in human disease [ 30 ā€“ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomics is a technology enabling significantly and profoundly better approach to investigating and understanding proteins' function and their posttranslational modifications [7][8][9][10][11][12]. Applying proteomics methods for analysis of clinical samples is especially important in time of personalized medicine, which tailors individualized treatment of each patient based on specification of the diseases [3,[13][14][15][16][17][18][19]. Furthermore, (clinical) proteomics can be used as a method-of-choice for the screening of biomarkers used for early discovery and early diagnostics.…”
Section: Introductionmentioning
confidence: 99%